2019
DOI: 10.1177/0361198119849064
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Operational Effect of Narrow Lanes and Shoulders for the Highway Capacity Manual

Abstract: Unnecessary traffic delays and vehicle emissions have adverse effects on quality of life. To solve the traffic congestion problem in the U.S.A., mitigation or elimination of bottlenecks is a top priority. Agencies across the U.S.A. have deployed several congestion mitigation strategies, such as lane and shoulder width reduction, which aim to adding lanes without significantly altering the footprint of the freeway. A limited number of studies have evaluated the operational benefits of lane narrowing. Although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Because early CAV adoption is expected to be for heavy trucks (Hummer 2020), lighter vehicles were analysed as having no or only partial autonomy. Existing research on reduced lane widths for motorways (Kondyli, Hale et al 2019), coupled with industry guidance for using narrow lanes for temporary traffic management (Gregg 2007), were used to produce sub-standard, but feasible, lane widths. Also, innovative cross-section solutions were developed purposefully for this research, allowing the special wheel tracking capabilities (uniform and zero-wheel wander) of CATs to be accounted for.…”
Section: Stage 2 -Designmentioning
confidence: 99%
“…Because early CAV adoption is expected to be for heavy trucks (Hummer 2020), lighter vehicles were analysed as having no or only partial autonomy. Existing research on reduced lane widths for motorways (Kondyli, Hale et al 2019), coupled with industry guidance for using narrow lanes for temporary traffic management (Gregg 2007), were used to produce sub-standard, but feasible, lane widths. Also, innovative cross-section solutions were developed purposefully for this research, allowing the special wheel tracking capabilities (uniform and zero-wheel wander) of CATs to be accounted for.…”
Section: Stage 2 -Designmentioning
confidence: 99%
“…Kondyli et al. found a 22% drop in capacity in case of incidents or adverse weather; however, the authors did not distinguish between the two events ( 7 ). Finally, HCM6 suggested capacity adjustments in case of incidents, based on the number of lane closures on urban freeways (Table 1) (1).…”
Section: Introductionmentioning
confidence: 99%
“…They proposed two linear regression models to estimate incident capacity and capacity reduction under incident conditions as a function of incident category, total number of lanes, and number of closed lanes. Kondyli et al found a 22% drop in capacity in case of incidents or adverse weather; however, the authors did not distinguish between the two events (7). Finally, HCM6 suggested capacity adjustments in case of incidents, based on the number of lane closures on urban freeways (Table 1) (1).…”
Section: Introductionmentioning
confidence: 99%
“…Shackel et al conducted a study based on urban road observations and found that overtaking speed is influenced by road infrastructure and vehicle types, with wider lane widths often leading to increased overtaking speeds. 7,8 Kondyli et al 13 discovered that reducing lane and shoulder width has a significant effect on free-flow speeds, with a decrease of 1 m/h for every foot of width reduction. Godley et al 14 and other researchers found that narrowing the lane width to 3.0 m is an effective method for reducing driving speed compared to wider lanes.…”
Section: Introductionmentioning
confidence: 99%